Matt Yockey. Make Ours Marvel: Media Convergence and a Comics Universe. Austin: U of Texas P, 2017. - Kevin Degnan (Studies in 20th & 21st Century Literature, 2017)
Review of Matt Yockey. Make Ours Marvel: Media Convergence and a Comics Universe. Austin: U of Texas, 2017.
Keywords: Superheroes; comics; film; history